Results after En Bloc Lateral Wall Decompression Surgery with Orbital Fat Resection in 111 Patients with Graves’ Orbitopathy - Nicole Fichter; Rudolf F. Guthoff (International Journal of Endocrinology)
Purpose. To evaluate the effect of en bloc lateral wall decompression with additional orbital fat resection in terms of exophthalmos reduction and complications. Methods. A retrospective, noncomparative case series study from 1999 to 2011 (chart review) in Graves’ orbitopathy (GO) patients. The standardized surgical technique involved removal of the lateral orbital wall including the orbital rim via a lid crease approach combined with additional orbital fat resection. Exophthalmos, diplopia, retrobulbar pressure sensation, and complications were analyzed pre- and postoperatively. Results. A total of 111 patients (164 orbits) with follow-up >3 months were analysed. Mean exophthalmos reduction was 3.05mm and preoperative orbital pressure sensation resolved or improved in all patients. Visual acuity improved significantly in patients undergoing surgery for rehabilitative or vision threatening purposes. Preoperative diplopia improved in 10 patients (9.0%) but worsened in 5 patients (4.5%), necessitating surgical correction in 3 patients. There were no significant complications; however, one patient had slight hollowing of the temporalis muscle around the scar that did not necessitate revision, and another patient with a circumscribed retraction of the scar itself underwent surgical correction. Conclusions. The study confirms the efficiency of en bloc lateral wall decompression in GO in a large series of patients, highlighting the low risk of disturbance of binocular functions and of cosmetic blemish in the temporal midface region.